Perancangan dan Implementasi Sistem Informasi Presensi Pegawai Berbasis Web Menggunakan Fingerspot pada KPP Pratama - Alex Ristanto Pratama; Eko Siswanto; Toni Wijanarko Adi Putra; Budi Hartono; Arsito Ari Kuncoro (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
Employee attendance is a crucial component of human resource management, particularly in government institutions such as the Tax Service Office (KPP) Pratama. The manual attendance system previously used is prone to fraud, inefficient in data processing, and time-consuming during recap. This study aims to design and implement a web-based employee attendance information system integrated with Fingerspot biometric devices to improve accuracy, security, and efficiency in attendance management. The research employs the Research and Development (R&D) method using the Borg & Gall model, which includes stages of preliminary study, system design, product development, expert validation, limited trials, revisions, and implementation. The system was developed using the Laravel (PHP) framework and a MySQL database, integrated with the Fingerspot API to synchronize attendance data in real time. Validation results from three experts produced an average feasibility score of 4.32 out of 5, indicating that the system is highly suitable for use. Trials conducted with 10 KPP Pratama employees showed that 90% of respondents found the system more practical and 100% stated that it effectively prevents attendance fraud. Furthermore, the monthly attendance recap time was significantly reduced from 3 days to less than 1 hour. Therefore, this system has proven to be a reliable digital solution that supports transparent and accountable personnel management within KPP Pratama.